2022
DOI: 10.3847/2041-8213/ac9ab2
|View full text |Cite
|
Sign up to set email alerts
|

A First Look at the Abundance Pattern—O/H, C/O, and Ne/O—in z > 7 Galaxies with JWST/NIRSpec

Abstract: We analyze the rest-frame near-UV and optical nebular spectra of three z > 7 galaxies from the Early Release Observations taken with the Near-Infrared Spectrograph (NIRSpec) on the James Webb Space Telescope (JWST). These three high-z galaxies show the detection of several strong emission nebular lines, including the temperature-sensitive [O iii] λ4363 line, allowing us to directly determine the nebular conditions and abundances for O/H, C/O, and Ne/O. We derive O/H abundances and ionization parameters that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 65 publications
7
61
1
Order By: Relevance
“…Mrk 71 is one of the most nearby (distance = 3.4 Mpc) analogues to high-z star-forming galaxies, with high electron temperature (T e ∼ 15, 000 K), high ionisation parameter (log U ∼ −2.2), and compact morphology, which are consistent with young starbursts (stellar age of the primary western component is ∼ 1 Myr) [16]. Such properties are extreme among nearby galaxies, but common in star-forming galaxies at z ≳ 2 [17][18][19][20] and similar to recent JWSTbased measurements at z ≳ 8 [5][6][7]. Moreover, low dust attenuation in Mrk 71 makes it especially suitable for comparing optical and infrared (IR) fluxes.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Mrk 71 is one of the most nearby (distance = 3.4 Mpc) analogues to high-z star-forming galaxies, with high electron temperature (T e ∼ 15, 000 K), high ionisation parameter (log U ∼ −2.2), and compact morphology, which are consistent with young starbursts (stellar age of the primary western component is ∼ 1 Myr) [16]. Such properties are extreme among nearby galaxies, but common in star-forming galaxies at z ≳ 2 [17][18][19][20] and similar to recent JWSTbased measurements at z ≳ 8 [5][6][7]. Moreover, low dust attenuation in Mrk 71 makes it especially suitable for comparing optical and infrared (IR) fluxes.…”
supporting
confidence: 80%
“…Our far-IR result is inconsistent (∼ 2.5σ significance) with the metallicity from recombination lines and instead indicates little to no bias in the standard T e method, ruling out the long-standing hypothesis that the ADF is explained by temperature fluctuations [4] for this object. Our results provide a framework to accurately measure metallicity across cosmic history, including with recent data reaching within the first billion years with JWST [5][6][7] and the Atacama Large Millimeter Array (ALMA) [8,9].…”
mentioning
confidence: 96%
“…The JWST ERO spectroscopic data of S04590 have already been presented and examined by a number of independent studies (Arellano-Córdova et al 2022;Brinchmann 2022;Carnall et al 2023;Curti et al 2023;Katz et al 2023;Rhoads et al 2023;Schaerer et al 2022;Tacchella et al 2022;Taylor et al 2022;Trump et al 2022). The NIRSpec spectroscopy is obtained with the medium-resolution gratings G235M/F170LP (1.75-3.1 μm) and G395M/F290LP (2.9-5.2 μm), with 1000  l l = D = (Jakobsen et al 2022), for a total exposure time of 8754 s. We use the JWST pipeline to perform the standard wavelength, flat-field, and photometric calibrations to the individual NIRSpec exposure files.…”
Section: Nirspec Spectroscopymentioning
confidence: 99%
“…We fix the redshift to the spectroscopic NIRSpec redshift z spec = 8.496 (see Section 3.3). We include nebular emission via CLOUDY (Ferland et al 2017), allowing the ionization parameter, U, to vary within ( ) U 3 log 1 10 -< <to account for the typically higher ionization parameter at z  6 (Sugahara et al 2022), and the derived electron temperature (see, e.g., Arellano-Córdova et al 2022;Curti et al 2023;Katz et al 2023;Trump et al 2022; and the section below). We assume a Salim et al (2018) attenuation curve, which is notably steeper than the typically adopted Calzetti extinction curve (Calzetti et al 2000).…”
Section: Modeling the Sedmentioning
confidence: 99%
“…With the recent advent of JWST science operations, galaxyevolution studies will be revolutionized by the unrivaled infrared spectroscopy capabilities the telescope offers. Indeed, the promise of JWST/Near Infrared Spectrograph (NIRSpec) to transform high-redshift direct-method metallicity studies is already being demonstrated with the recent detection of [O III] λ4363 in three lensed z > 7 galaxies (Arellano-Córdova et al 2022;Brinchmann 2022;Carnall et al 2022;Curti et al 2022;Katz et al 2022;Schaerer et al 2022;Trump et al 2022). One of the key improvements offered by JWST for near-infrared spectroscopic observations is the removal of the challenges associated with observing through the Earth's atmosphere.…”
Section: Prospects For Direct-methods Abundances With Jwstmentioning
confidence: 99%